1997
DOI: 10.1007/bf02767130
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stretch increases intracellular calcium concentration in cultured ventricular cells from neonatal rats

Abstract: We investigated the effects of mechanical stretch on intracellular calcium concentration ([Ca2+]i) of cultured neonatal rat ventricular cells using microfluorometry with fura-2. Myocytes were cultured on laminin-coated silicon rubber and stretched by pulling the rubber with a manipulator. Myocytes were either mildly stretched (to less than 11.5% of control length), moderately so (to 115%-125% of control length), or extensively (to over 125% of the control length). "Quick stretches" (accomplished within 10s) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Furthermore, some previous studies reported that an acute stretch can also trigger a Ca 2ϩ release from the sarcoplasmic reticulum through ryanodine receptors. 31,32 In our experiments, however, the stretch-induced excitations were still observed after administration of ryanodine. Moreover, changes in the extracellular calcium concentration did not affect the stretch-induced excitability.…”
Section: Heterogeneity In the Tissue Structure For Bridging Cellular mentioning
confidence: 41%
“…Furthermore, some previous studies reported that an acute stretch can also trigger a Ca 2ϩ release from the sarcoplasmic reticulum through ryanodine receptors. 31,32 In our experiments, however, the stretch-induced excitations were still observed after administration of ryanodine. Moreover, changes in the extracellular calcium concentration did not affect the stretch-induced excitability.…”
Section: Heterogeneity In the Tissue Structure For Bridging Cellular mentioning
confidence: 41%
“…Cardiac myocytes exhibit activation of SACs, which is inhibited by Gd 3ϩ (24,37,40). Activation of SACs in heart cells can lead to changes in fluxes of Ca 2ϩ , Na ϩ , or K ϩ cations (7,8,35,37,39,40), which may affect the myocardial contractile state.…”
Section: Discussionmentioning
confidence: 99%
“…Filling of the coronary vessels will change hoop (circumferential) stress in the vessel wall, thereby mechanically deforming the membranes of myocardial cells. Mechanical deformation of cardiomyocytes activates stretch-activated ion channels (SACs) (24,27,28,37,39,40), thereby conducting Ca 2ϩ , Na ϩ , or K ϩ cations (7,8,35,37,39,40), which may affect the contractile state of the myocardium. Besides hoop stress, a change in perfusion will change also shear stress and may thereby induce endothelium-dependent nitric oxide (NO) release.…”
mentioning
confidence: 99%
“…The second phase, the slow force response, seems to result from a slow rise in [Ca 2ϩ ] i , supporting the data reported by Allen and Kurihara (3). Stretching of isolated single cardiomyocytes led to an increase in [Ca 2ϩ ] i via SACs in the guinea pig (11), chick (40), and neonatal rat (42). Because the increase of [Ca 2ϩ ] i to myocardial stretch occurred during systole and not diastole, the involvement of SACs in the slow force response in muscle preparations was criticized by Kentish and Wrzosek (26) (23); and 4) the time course of the increase of peak [Ca 2ϩ ] i is too slow to be caused by activation of stretch-induced inward cation currents via SACs, which are normally activated within 10 ms in rat ventricular myocytes (9,45).…”
Section: Discussionmentioning
confidence: 99%